Gender Differences in Acute Coronary Syndrome in Arab Emirati Women—Implications for Clinical Management. (January 2013) - Shehab, Abdulla; Yasin, Javed; Hashim, Muhammad Jawad; Al-Dabbagh, Bayan; Mahmeed, Wael Al; Bustani, Nazar; Agrawal, Amrish; Yusufali, Afzalhussein; Wassef, Adel; Alnaeemi, Abdulla
Gender differences exist in many aspects of acute coronary syndrome (ACS), including presentation and delay in diagnosis and treatment. The aim of the study was to evaluate gender-related differences in ACS patients in the United Arab Emirates (UAE). We analyzed a subset (n = 1697) of the Gulf Registry of Acute Coronary Events (Gulf RACE) data collected in 2007 of patients with ACS from 18 UAE hospitals. Women were significantly older (mean age: 64.0 ± 12.4 years for females and 50.9 ± 10.6 years for males, P < .001), more often had cardiac risk factors and were significantly less treated with β-blockers and reperfusion therapy. The adjusted mortality rate of women was 4.6% versus 1.2% in men ( P < .001). Heart failure was higher in females compared with men (24.6% vs 12.5%; P < .001). Reasons for the high in-hospital mortality in women need to be investigated further.